2017
DOI: 10.1016/j.phro.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

The normal tissue sparing potential of an adaptive plan selection strategy for re-irradiation of recurrent rectal cancer

Abstract: Background and purpose: Radiotherapy (RT) of rectal cancer is challenged by potentially large interfractional anatomy changes. The risk of radiation-induced morbidity is a particular concern in patients receiving re-irradiation for recurrent disease. We propose an adaptive RT plan selection strategy for these patients and report on its clinical feasibility and normal tissue sparing potential. Material and methods: Eight patients with pelvic recurrence were re-irradiated according to a hyperfractionation protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Passoni et al and Raso et al [31,32] also reported on an adaptive procedure, but applied to the boost of the residual tumor during the last 6 fractions of LCRT. Byskov et al [33] describe an adaptive approach to re-irradiation of rectal recurrence. As neither strategy is applied to the mesorectum, they cannot easily be compared.…”
Section: Discussionmentioning
confidence: 99%
“…Passoni et al and Raso et al [31,32] also reported on an adaptive procedure, but applied to the boost of the residual tumor during the last 6 fractions of LCRT. Byskov et al [33] describe an adaptive approach to re-irradiation of rectal recurrence. As neither strategy is applied to the mesorectum, they cannot easily be compared.…”
Section: Discussionmentioning
confidence: 99%
“…Online adaption using a plan library is well suited for tumours with predictable, potentially large and frequent interfractional anatomical variations while intrafraction changes remain comparatively small. Examples are bladder [11] , [12] , cervix [13] , [14] or rectum [15] , [16] , [17] where different bladder or rectal fillings can be anticipated and a library of plans covering several scenarios are made available for treatment. Online daily replanning can address any type of anatomical changes but is the most resource-demanding approach and as such, its clinical implementation has only been demonstrated in few treatment sites and institutions so far [18] , [19] , [20] , [21] , [22] .…”
mentioning
confidence: 99%
“…Currently, IMRT or VMAT is the standard technique for reRT in our institution. A recent planning study demonstrated that with IMRT, the margins can be reduced, yielding considerable normal tissue sparing [33]. Also, preliminary data on proton therapy in this field are promising [34].…”
Section: Discussionmentioning
confidence: 99%